Online Psychological Counseling to Reduce Suicidal Ideation and Improve Emotional Regulation in Students Under Academic Pressure - Lailatul Izzah; Eva Yuliza; Sunarsih Sunarsih; Raspan Hamdi; Renny Rahmalia; Yusniar Siregar; Elvina Rahmi (Jurnal Masyarakat Mengabdi, 2026)
Mental health problems among final-year university students are increasing due to academic and psychosocial pressures, often leading to emotional dysregulation and suicidal ideation. Online counseling offers a flexible and accessible intervention model. This study used a qualitative case-based approach במסגרת a community service (PkM) program. The participant was a university student (“Aya”) experiencing severe psychological distress, including self-harm and suicidal ideation. The intervention integrated crisis intervention, Cognitive Behavioral Therapy (CBT), and Dialectical Behavior Therapy (DBT), conducted through stages of crisis stabilization, cognitive restructuring, emotional regulation training, and strengthening social support. Data were obtained from counseling session notes, observation, and reflective evaluation. Findings indicated significant improvement in the participant’s psychological condition. Suicidal ideation and self-harm behaviors decreased substantially. The participant demonstrated more adaptive thinking patterns and improved emotional regulation through coping strategies such as breathing techniques and positive distraction. Social support also functioned as a protective factor. Integrative online psychological intervention is effective in reducing distress and suicide risk while enhancing emotional regulation. This model has strong potential as an adaptive mental health service in higher education.